Effect of plant growth regulators on growth, flowering and corm production of gladiolus cv. Snow Princess - Kumar, P Naveen; Misra, R L (The Indian Journal of Agricultural Sciences, 2012)
The earliness in sprouting was observed with all the treatments of IAA and GA3 irrespective of the concentrations, however, the earliest (10.00 days) was recorded in corms dipped in GA3 (1 000 ppm). GA3 was found to be the best in increasing the floret diameter, number of florets/spike, rachis length and field durability of spike and in earliness to flowering. The number of cormels/plant and volume were highly increased by IAA treatment. Both IAA and GA3 were found equally effective in increasing the weight of corm and cormels, diameter of the corm and propagation coefficient, spike length, leaf area and early sprouting of the corms. Among the different modes of application, soaking treatment helps in the efficient absorption of the growth regulator solutions and its effect on sprouting and early vegetative growth is pronounced whereas spraying influences the corm characters and to some extent the flowering behaviour. Soaking + spraying treatment had lasting effect throughout the crop period and hence was superior to all other treatments.